Engaging Minority Girls in Organized Youth Sport in Norway: A Case Study of a Project That Worked - Gjesdal, Siv; Hedenborg, Susanna (Frontiers in Sports and Active Living, 2021)
Sport participation is considered a positive pastime endower that can offer a range of positive outcomes for children and youths. It has also increasingly been recognized as a potentially important context for fostering social inclusion for minority youths. Yet across Europe, minority girls are participating in sport to a lesser degree than their majority counterparts. Using self-determination theory (SDT) and the social ecological model as the framework, this study explored the reasons why a particular project aimed at recruiting minority girls to organized team sport succeeded in doing just that. A case study design was adopted to provide an in-depth analysis of how this project satisfied the basic psychological needs of minority girls. Nine girls, four parents, two coaches, and two project team members were interviewed about the project and sport participation in general. Data were analyzed using thematic analysis. Two main themes were identified, a sense of being facilitated and inclusion in the sport environment. The former emphasized the importance of aligning the participation with the girls' cultural norms and values, particularly in the beginning. It also included practical issues such as finances, reminding us that participation in sport is not just a motivational issue. The latter focused on the importance of including the girls in the general sports program, regardless of their athletic abilities at the onset of their participation and creating a mastery environment. Moreover, by removing remediable differences between the minority and majority girls, such as having the right equipment, seemed important to fostering a sense of belonging in the sports club. Additionally, establishing meaningful relationships with coaches and majority counterparts seemed to be a major motivating factor.